Strategi dan Hambatan dalam Pemberantasan Handphone, Pungutan Liar, dan Narkotika di Lembaga Pemasyarakatan - Barlian, Ridho Saputra; Dewi, Erna; Monica, Dona Raisa (Journal of Contemporary Law Studies, 2024)
This study aims to analyze the efforts made by correctional institutions to eradicate the use of cell phones, extortion practices, and narcotics distribution among inmates. The research employs a normative juridical approach, with data collected through literature review and qualitatively analyzed to draw comprehensive conclusions. The findings indicate that eradication efforts are conducted through two main approaches: prevention and enforcement. Prevention measures include inspecting visitors, providing legal and narcotics education to inmates, and conducting narcotics tests on inmates. Enforcement actions involve conducting raids on inmates, investigating inmates suspected of narcotics distribution within the prison, and legally processing inmates who commit narcotics-related crimes. However, the study also identifies several obstacles to these efforts. A significant barrier is the limited technology available to detect the presence of cell phones and narcotics within the prison. Additionally, there are challenges posed by individuals who smuggle cell phones and narcotics into correctional facilities, which complicates the institution's efforts to address these issues. In conclusion, while correctional institutions have undertaken various measures to combat the use of cell phones, extortion, and narcotics, there are ongoing challenges that require further attention, particularly in enhancing technology and supervision to reduce external smuggling.